Neural correlates of musical timbre: an ALE meta-analysis of neuroimaging data - Bellmann, Oliver Tab; Asano, Rie (Frontiers in Neuroscience, 2024)
Timbre is a central aspect of music that allows listeners to identify musical sounds and conveys musical emotion, but also allows for the recognition of actions and is an important structuring property of music. The former functions are known to be implemented in a ventral auditory stream in processing musical timbre. While the latter functions are commonly attributed to areas in a dorsal auditory processing stream in other musical domains, its involvement in musical timbre processing is so far unknown. To investigate if musical timbre processing involves both dorsal and ventral auditory pathways, we carried out an activation likelihood estimation (ALE) meta-analysis of 18 experiments from 17 published neuroimaging studies on musical timbre perception. We identified consistent activations in Brodmann areas (BA) 41, 42, and 22 in the bilateral transverse temporal gyri, the posterior superior temporal gyri and planum temporale, in BA 40 of the bilateral inferior parietal lobe, in BA 13 in the bilateral posterior Insula, and in BA 13 and 22 in the right anterior insula and superior temporal gyrus. The vast majority of the identified regions are associated with the dorsal and ventral auditory processing streams. We therefore propose to frame the processing of musical timbre in a dual-stream model. Moreover, the regions activated in processing timbre show similarities to the brain regions involved in processing several other fundamental aspects of music, indicating possible shared neural bases of musical timbre and other musical domains.